1970
DOI: 10.4314/ejhs.v28i5.14
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Its Association with Anemia among Pregnant Women Attending Public Health Facilities in South Ethiopia

Abstract: BACKGROUND: Anemia is a major public health problem among pregnant women in developing countries like Ethiopia. Nutritional deficiency related to anemia is an important contributor to maternal mortality and poor fetal outcomes.METHODS: Institution based cross-sectional study was conducted among pregnant women to assess the prevalence of anemia and its association with dietary diversity in Hossana Town from March 15 to April 30, 2017. Systematic random sampling procedure was employed to select 314 study subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
5
27
1
2
Order By: Relevance
“…For example, in relation to diets, the consumption of animal-sourced foods was indicated as one of the ways to prevent anaemia. Evidence suggests that dietary diversity is associated with lower anaemia risk (Delil et al, 2018). In addition, the consumption of vegetables and legumes was mentioned as one of the pathways to preventing anaemia or reducing its incidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in relation to diets, the consumption of animal-sourced foods was indicated as one of the ways to prevent anaemia. Evidence suggests that dietary diversity is associated with lower anaemia risk (Delil et al, 2018). In addition, the consumption of vegetables and legumes was mentioned as one of the pathways to preventing anaemia or reducing its incidence.…”
Section: Discussionmentioning
confidence: 99%
“…17.12, 61.41; I 2 = 99.7%, p ≤ .01), and this was computed using nine studies (Abriha et al, 2014;Kobiro et al, 2020;Delil et al, 2018;Demilew et al, 2020;Jemal & Awol, 2019;Kumera et al, 2015;Lebso et al, 2017;Samuel et al, 2020;Workicho et al, 2019). High DDS was also computed for lactating women using five studies Duko et al, 2018;Eramo, 2018;Julla et al, 2018;Tikuye et al, 2019), and it was found to be 9.1% (95% CI: 4.01, 14.16; I 2 = 98%, p ≤ .01) (Figure 2).…”
Section: Pooled Prevalence Of Dds and Mdd Among Pregnant And Lactating Women In Ethiopiamentioning
confidence: 99%
“…The pooled low DDS was computed from 15 studies, of which eight (Abriha et al, 2014;Kobiro et al, 2020;Delil et al, 2018;Demilew et al, 2020;Jemal & Awol, 2019;Kumera et al, 2015;Lebso et al, 2017;Samuel et al, 2020) of the studies were among pregnant women and six Duko et al, 2018;Eramo, 2018;Julla et al, 2018;Tikuye et al, 2019;Weldehaweria et al, 2016) 2). Similarly, the pooled prevalence of medium DDS was computed among six studies (Abriha et al, 2014;Kobiro et al, 2020;Delil et al, 2018;Lebso et al, 2017;Samuel et al, 2020;Workicho et al, 2019) on pregnant women and six studies Duko et al, 2018;Eramo, 2018;Julla et al, 2018;Tikuye et al, 2019;Weldehaweria et al, 2016) 2). In addition, the pooled prevalence of high DDS among pregnant and lactating women in Ethiopia was found to be 28.73% (95% CI: 12.94, 44.52; I 2 = 99.9%, p ≤ .01).…”
Section: Pooled Prevalence Of Dds and Mdd Among Pregnant And Lactating Women In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Rich dietary sources of iron include meat especially offal (organ meat), fish, eggs, poultry, and meat extracts [14]. Whereas bread and flour, breakfast cereals, dark green vegetables, pulses, nuts, dried fruits like prunes, figs, and apricots are good sources of iron.…”
Section: Introductionmentioning
confidence: 99%